Inhibitory Effect of Light on Growth-Supporting Properties of Eosin Methylene Blue Agar - Girolami, R. L. (1976)
Exposure of eosin methylene blue agar to visible light can alter the ability of that medium to support microbial growth. Proteus species were most sensitive to the photodynamic action.